1991
DOI: 10.1038/hdy.1991.7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pollination environment manipulation on the apparent outcrossing rate in a Douglas-fir seed orchard

Abstract: The mating system of Douglas-fir [Pseudotsuga menziesii (Mirb.) Franco] was examined in two genetically similar seed orchard blocks with the aid of allozyme polymorphisms at six loci. The pollination environment (time of pollination and length of pollination season) of one block was manipulated by means of an overhead water spray cooling treatment. The cooling treatment temporarily delayed the pollination season in the treated block by 12 days relative to the untreated one. In addition, the length of the polli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
(10 reference statements)
0
16
1
Order By: Relevance
“…Under panmixia, a selfing rate of 2% is expected to occur in this seed orchard (49/49 2 ); however, an estimate of 15.2% was detected. This value is higher than most selfing rates reported for this species' natural and/or seed orchard populations (El-Kassaby and Davidson, 1991;Ritland and El-Kassaby, 1985;Shaw and Allard, 1982;Slavov et al, 2005) and is unexpected for the following reasons: (1) pollination environment was manipulated by the bloom delay treatment which has been shown to promote outcrossing because all parents released their pollen within a limited timeframe (El-Kassaby and Davidson, 1991;El-Kassaby and Ritland, 1986;El-Kassaby et al, 1988), (2) SMP was used which also has been proven to increase outcrossing specifically if outside SMP donors were used (ElKassaby and Davidson, 1990), and (3) the seed orchard was exposed to external gene flow (see pollen contamination section below) which is expected to increase outcrossing because every successful pollen contamination event is an outcrossing event (El-Kassaby and Ritland, 1986). It could be speculated that SMP from the 12 internal parents unintentionally increased the selfing rate through application on donor clones; however, this possibility should be ruled out since pollen mixes were exclusively applied to non-pollen donors.…”
Section: Selfingcontrasting
confidence: 45%
“…Under panmixia, a selfing rate of 2% is expected to occur in this seed orchard (49/49 2 ); however, an estimate of 15.2% was detected. This value is higher than most selfing rates reported for this species' natural and/or seed orchard populations (El-Kassaby and Davidson, 1991;Ritland and El-Kassaby, 1985;Shaw and Allard, 1982;Slavov et al, 2005) and is unexpected for the following reasons: (1) pollination environment was manipulated by the bloom delay treatment which has been shown to promote outcrossing because all parents released their pollen within a limited timeframe (El-Kassaby and Davidson, 1991;El-Kassaby and Ritland, 1986;El-Kassaby et al, 1988), (2) SMP was used which also has been proven to increase outcrossing specifically if outside SMP donors were used (ElKassaby and Davidson, 1990), and (3) the seed orchard was exposed to external gene flow (see pollen contamination section below) which is expected to increase outcrossing because every successful pollen contamination event is an outcrossing event (El-Kassaby and Ritland, 1986). It could be speculated that SMP from the 12 internal parents unintentionally increased the selfing rate through application on donor clones; however, this possibility should be ruled out since pollen mixes were exclusively applied to non-pollen donors.…”
Section: Selfingcontrasting
confidence: 45%
“…The Gsr value for the 49 NPs was 0.045, typical of that reported for Douglas-fir and most coniferous trees (Mouna, 1989;E1-Kassaby, 1991;Hamrick et al, 1992). The Gsr values of the domesticated populations were much lower, being 0.010, 0.013, and 0.015 for the 1GSOs before and after roguing and the 2GSOs, repectively.…”
Section: Distribution Of Variationmentioning
confidence: 83%
“…is lost, in a sample of N individuals. (Aspit et aL, 1989;Roberds et al, 1991;EI-Kassaby and Ritland, 1992;Nakamura and Wheeler, 1992), female reproductive success (EI-Kassaby et aL, 1989;Reynolds and E1-Kassaby, 1990;E1-Kassaby and Cook, 1994), as well as differences of reproductive phenology among the seed orchard parents (E1-Kassaby et al, 1988;Erickson and Adams, 1989;EI-Kassaby and Askew, 1991;Copes and Sniezko, 1991;E1-Kassaby and Davidson, 1991). These factors cause restricted mating among individuals, and thus increase the rate of random genetic drift and its effects on the depletion of the genetic variability.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, however, have shown that variation in reproductive phenology has significant effects on the mating system of Douglas fir (El-Kassaby and Davidson 1991;El-Kassaby et al 1986;Erickson and Adams 1989;Sorensen 1997). Related individuals tend to have similar reproductive phenology, and thus may have a higher probability of pollinating each other than unrelated individuals, particularly if their reproductive phenology is extremely early or late.…”
Section: Predicting Inbreeding Depression Indices Of a Seed Orchard Wmentioning
confidence: 93%